KAJIAN FARMAKOGNOSTIK KULIT BATANG BALIK ANGIN (Mallotus paniculatus (Lam.) Mull. Arg) - Fitriyanti; Nopita; Revita Saputri (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
ABSTRACTIndonesia is rich with natural products that can be used as a medicine. One of thenatural resources used traditionally in Borneo is Balik Angin stem bark as amedicine for diarrhea and swollen gums. In terms of its potential, it is necessaryto research to provide a scientific basis for qualitatively describingpharmacognostic which includes organoleptic, macroscopic and microscopic anddetermining the identification of chemical compounds contained through reactiontests and thin layer chromatography profiles of ethanol extract 70%. Theorganoleptic test has the results in the form of a distinctive odor, brown color,and a feeling of tightness. In the macroscopic observation of the Stem bark hasthick bark with a hard, coarse and cracked texture with a thin outer surface darkbrown easy to peel and red gummy. Microscopic observations have identifiable fragments in the form of epidermal cells, cortex, and crystal oxalate. Theidentification of chemical compounds showed positive effects on tannins,saponins, flavonoids, triterpenoids, and quinones. Profile of TLC obtained 5stains separated by eluent ethyl acetate: methanol: water with (7: 2: 1). Keywords : Mallotus paniculatus (Lam.) Mull. Arg, Pharmacognostic study,ethanol extract 70%.